1992
DOI: 10.1128/aac.36.8.1630
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecylphosphocholine: oral treatment of visceral leishmaniasis in mice

Abstract: Hexadecylphosphocholine (He-PC), a novel phospholipid derivative, was tested against Leishmania donovani and Leishmania infantum, the causative agents of visceral leishmaniasis. In vitro, promastigotes were highly susceptible to He-PC; the 50% inhibitory concentrations were between 0.89 and 2.25 micrograms/ml for the different leishmanial strains. In vivo, a marked antileishmanial activity in infected BALB/c mice could be demonstrated after oral administration of He-PC. Whereas parasite suppression and killing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
97
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 27 publications
2
97
0
4
Order By: Relevance
“…Antileishmanial activity is expressed as IC 50 , which is a measure of the concentration of test substance that inhibits 50% of parasite growth. The IC 50 values obtained with ketoconazole were 26 ng/ml, 13 Ag/ml for miltefosine and 80 -100 ng/ml for amphotericin B, results which are comparable to published values for these compounds (Berman et al, 1984;Kuhlencord et al., 1992; Golenser et al, 1999, respectively). The results presented above and in Figs.…”
supporting
confidence: 88%
“…Antileishmanial activity is expressed as IC 50 , which is a measure of the concentration of test substance that inhibits 50% of parasite growth. The IC 50 values obtained with ketoconazole were 26 ng/ml, 13 Ag/ml for miltefosine and 80 -100 ng/ml for amphotericin B, results which are comparable to published values for these compounds (Berman et al, 1984;Kuhlencord et al., 1992; Golenser et al, 1999, respectively). The results presented above and in Figs.…”
supporting
confidence: 88%
“…Portanto, a toxicidade e o índice de recidivas e resistência às drogas justificam a busca de novas drogas para tratar a leishmaniose tegumentar 1 2 4 12 14 15 . A miltefosina (hexadecilfosfocolina), medicamento originalmente desenvolvido como antineoplásico, tem ação eficaz sobre as leishmânias 5 7 8 9 16 18 19 20 22 . Esta droga age interferindo na membrana celular do parasita, sem interagir com o DNA, depois modula a composição lipídica, a permeabilidade e fluidez da membrana, assim como o metabolismo de fosfolipídeos, induzindo morte celular por apoptose 11 22 .…”
unclassified
“…In addition, they are active against several protozoan parasites such as Leishmania donovani (1,17), Trypanosoma cruzi (23), and Entamoeba histolytica (24). In humans, a clinical study demonstrated that visceral leishman-iasis could be treated successfully by oral treatment with hexadecylphosphocholine (APC1) (10).…”
mentioning
confidence: 99%